Caracterización de Patógenos Causantes de Mastitis Clínica y Subclínica y Perfil de Sensibilidad “In Vitro” en Dos Fincas con Diferentes Condiciones Climáticas (2022)
The objective of this study was to characterize the pathogens that cause clinical and subclinical bovine mastitis by means of specialized tests in two farms with different climatic conditions and, in turn, a comparison of results was carried out, since animals from both farms were worked with. To determine if this factor interferes in the presentation of the different microorganisms. Additionally, an "in vitro" sensitivity profile of the pathogens was carried out to determine the efficacy of the most used antibiotics in these places, considering the great importance of this aspect when seeking the best treatment for animals with mastitis. The research that has been developed is of a correlational type, aimed at animal welfare and health, carried out with a sample of 36 milking cows from both farms. The main technique used was the collection of samples with the CMT test, cultures and antibiograms. It was obtained as a result that the predominant pathogens were Staphylococcus spp and Staphylococcus aureus and with less presentation: E. coli, Citrobacter diversus and Klebisella oxytoca. And that the microorganisms of farm # 1 have a greater resistance to cephalexin, amikacin, penicillin, ampicillin and amoxacillin + clavulanic acid, while the animals of farm # 2 have greater resistance to amikacin and to a lesser extent to ampicillin and amoxacillin + clavulanic acid.